TI_GERICHTE 11.2011.21 vom 30. Mai 2013 , Estinzione di una servitù di passo convenzionale o di un accesso necessario - TI Tribunale d'appello (2013)
Estinzione di una servitù di passo convenzionale o di un accesso necessario